The Analysis of Gene Expression Data Incorporating Tumor Purity Information - Ahn, Seungjun; Grimes, Tyler; Datta, Somnath (Frontiers in Genetics, 2021)
The tumor microenvironment is comprised of tumor cells, stroma cells, immune cells, blood vessels, and other associated non-cancerous cells. Gene expression measurements on tumor samples are an average over cells in the microenvironment. However, research questions often seek answers about tumor cells rather than the surrounding non-tumor tissue. Previous studies have suggested that the tumor purity (TP) – the proportion of tumor cells in a solid tumor sample – has a confounding effect on differential expression analysis of high versus low survival groups. We investigate three ways incorporating the TP information in the two statistical methods used for analyzing gene expression data, namely, differential network analysis (DNA) and differential expression analysis (DEA). Analysis 1 ignores the TP information completely, Analysis 2 uses a truncated sample by removing the low TP samples, and Analysis 3 uses TP as a covariate in the underlying statistical models. We use three gene expression data sets related to three different cancers from the Cancer Genome Atlas (TCGA) as test beds for our investigation. The networks from Analysis 2 have greater amount of differential connectivity in the two networks than that from Analysis 1 in all three cancer datasets. Similarly, Analysis 1 identified more differentially expressed genes than Analysis 2. Results of DNA and DEA using Analysis 3 were mostly consistent with those of Analysis 1 across three cancers. However, Analysis 3 identified additional cancer related genes in both DNA and DEA. Our findings suggest that using TP as a covariate in a linear model is appropriate for DEA, but a more robust model is needed for DNA. However, in the absence of ground truth, it is impossible to assess the accuracies of any of these methods. One option will be to study the statistical properties of these methods in simulated data sets which may be pursued elsewhere.